How did amber get its aquatic insects? Water-seeking polarotactic insects trapped by tree resin. (3rd June 2021) - Horváth, Gábor; Egri, Ádám; Meyer-Rochow, V. Benno; Kriska, György
ABSTRACT: Amber contains numerous well-preserved adult aquatic insects (e.g., aquatic beetles – Coleoptera, water bugs – Heteroptera, dragonflies – Odonata, caddisflies – Trichoptera, mayflies – Ephemeroptera, stone flies – Plecoptera). Since amber is fossilised resin of terrestrial conifer trees, it is an enigma how aquatic insects have ended up in the resin. Based on field studies in a Hungarian forest along a freshwater creek we suggest that tree resin traps water-seeking flying polarotactic aquatic insects because of its property to polarise reflected light. The sticky tree resin was modelled by a water-proof, transparent, colourless insect-monitoring glue laid on vertical and horizontal fallen tree trunks next to the creek. Adults of various polarotactic aquatic insect species were trapped only by the horizontal sticky trunk. In earlier field experiments we showed that these insects find water by means of the horizontal polarisation of water-reflected light, and therefore are attracted to and land on all surfaces which reflect horizontally polarised light. Using imaging polarimetry, we revealed the criterion of polarisation-based trapping by resiny tree trunks. According to our observations, flying aquatic insects can be trapped by sticky (resiny) regions of fallen tree trunks that reflect horizontally polarised light and thus attract polarotactic species. The resin continues to flow out of the trees even when fallen over or fractured in a storm. Our findings support and complement an earlier hypothesis, according to which amber-preserved adult aquatic insects have been trapped by resiny bark when they dispersed over land.